Postoperative standard chemoradiotherapy benefits primary glioblastoma patients of all ages. (18th December 2019) - Li, Guanzhang; Zhai, You; Wang, Zheng; Wang, Zhiliang; Huang, Ruoyu; Jiang, Haoyu; Li, Renpeng; Feng, Yuemei; Chang, Yuanhao; Jiang, Tao; Zhang, Wei
Abstract: Background: Glioblastoma is the most malignant tumor of the central nervous system. Several prediction models have been produced to aid in prognosis assessment. Age, a primary decision factor for prognosis, is associated with increased genomic alterations, however the exact link between increased age and poor prognosis is unknown. Objective: In this study, we aimed to reveal the underlying cause of poor prognosis in elderly patients. Methods: This study included data on 616 primary GBM tumor samples from the CGGA and TCGA databases and 41 nontumor brain tissue samples obtained from GSE53890 . Hallmarks and clinicopathological characteristics were evaluated in both tumor and nontumor brain tissues. The association between choice of treatment regimen and age was measured using ANOVA and Student's t test. Results: Age was a robust predictor of poor prognosis in glioma. No age‐related hallmarks of cancer were detected, including pathological characteristics or mutations. However, treatment choice was strongly significantly different between old and young patients. Combined chemo‐radiation therapy could benefit old and young GBM patients, however, old patients are currently less likely to choose it. Conclusion: The vast divergence in prognosis between young and old GBM patients is largely caused by choice of treatment rather than age‐related tumor genomic characteristics. Postoperative standard radio‐ and chemotherapy provide strong benefits to primary glioblastoma patients of all ages. Abstract : The main reason of poorer prognosis in elder patients was conservative treatment choosing, while standard radio‐ and chemotherapy should be generalized in all age grade of patients.